Impact of a potential 21st century "grand solar minimum" on surface temperatures and stratospheric ozone. Issue 16 (22nd August 2013) - Anet, J. G.; Rozanov, E. V.; Muthers, S.; Peter, T.; Brönnimann, S.; Arfeuille, F.; Beer, J.; Shapiro, A. I.; Raible, C. C.; Steinhilber, F.; Schmutz, W. K.
<x xml:space="preserve">Abstract</x> [1] We investigate the effects of a recently proposed 21st century Dalton minimum like decline of solar activity on the evolution of Earth's climate and ozone layer. Three sets of two member ensemble simulations, radiatively forced by a midlevel emission scenario (Intergovernmental Panel on Climate Change RCP4.5), are performed with the atmosphere‐ocean chemistry‐climate model AOCCM SOCOL3‐MPIOM, one with constant solar activity, the other two with reduced solar activity and different strength of the solar irradiance forcing. A future grand solar minimum will reduce the global mean surface warming of 2 K between 1986–2005 and 2081–2100 by 0.2 to 0.3 K. Furthermore, the decrease in solar UV radiation leads to a significant delay of stratospheric ozone recovery by 10 years and longer. Therefore, the effects of a solar activity minimum, should it occur, may interfere with international efforts for the protection of global climate and the ozone layer.